2021
DOI: 10.1371/journal.pone.0245294
|View full text |Cite
|
Sign up to set email alerts
|

The psychological effects of COVID-19 on hospital workers at the beginning of the outbreak with a large disease cluster on the Diamond Princess cruise ship

Abstract: The aim of the present study was to investigate the psychological effects of the COVID-19 outbreak and associated factors on hospital workers at the beginning of the outbreak with a large disease cluster on the Diamond Princess cruise ship. This cross-sectional, survey-based study collected demographic data, mental health measurements, and stress-related questionnaires from workers in 2 hospitals in Yokohama, Japan, from March 23, 2020, to April 6, 2020. The prevalence rates of general psychological distress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
7
17
0
7
Order By: Relevance
“…We then analyzed the quality of health using the 28-item General Health Questionary and found that the case rate was significantly higher in women than men (78.4 vs. 61.3%, p < 0.001). Our data is similar to other studies that report proportions between 45.8 and 80.6% ( 61 63 ). These results must be interpreted with caution, as women already have a worse self-reported quality of life, according to the analysis of the World Health Survey of 59 countries ( 64 ).…”
Section: Discussionsupporting
confidence: 92%
“…We then analyzed the quality of health using the 28-item General Health Questionary and found that the case rate was significantly higher in women than men (78.4 vs. 61.3%, p < 0.001). Our data is similar to other studies that report proportions between 45.8 and 80.6% ( 61 63 ). These results must be interpreted with caution, as women already have a worse self-reported quality of life, according to the analysis of the World Health Survey of 59 countries ( 64 ).…”
Section: Discussionsupporting
confidence: 92%
“…For healthcare workers other than physicians and nurses, one study reported that anxiety was significantly higher, but depression was comparable. 69 Another study conducted on a cruise ship during the early stages of the COVID-19 epidemic in Japan reported that distress was significantly stronger among clerical workers than physicians or nurses, 70 which are consistent with the results of the current study. Even in healthcare workers, inadequate medical knowledge was reported to be associated with increased levels of anxiety and depression.…”
Section: Discussionsupporting
confidence: 89%
“…Ide et al mentioned the psychological effects of the COVID-19 pandemic and associated factors on hospital workers at the beginning of the pandemic with the outbreak on the Diamond Princess cruise ship. 27 The study period of Ide et al was between the end of March and the beginning of April 2020, which was approximately half a month after ours. Healthcare providers at both high and low risks of infection who worked in hospitals and cared for patients with COVID-19 reported experiencing psychological distress at the beginning of the outbreak.…”
Section: Discussionmentioning
confidence: 69%
“…Healthcare providers at both high and low risks of infection who worked in hospitals and cared for patients with COVID-19 reported experiencing psychological distress at the beginning of the outbreak. 27 Feelings of being isolated and of discrimination or COVID-19-related stigmatisation were also investigated. 28 These feelings represent further stress that contributes to a mental health crisis.…”
Section: Discussionmentioning
confidence: 99%